Endothelium-dependent relaxation to acetylcholine in bovine oviductal arteries: mediation by nitric oxide and changes in apamin-sensitive K+ conductance. - García-Pascual, A. (1995)
1. Mechanisms underlying the relaxant response to acetylcholine (ACh) were examined in bovine oviductal arteries (o.d. 300-500 microns and i.d. 150-300 microns) in vitro. Vascular rings were treated with indomethacin (10 microM) to prevent the effects of prostaglandins. 2. ACh elicited a concentration-related relaxation in ring segments precontracted with noradrenaline (NA), which was abolished by endothelium denudation. 3. The ACh-induced relaxation was attenuated but not abolished by NG-nitro-L-arginine (L-NOARG, 1 microM-1 mM), an inhibitor of nitric oxide (NO) formation. The inhibition caused by L-NOARG (10 microM) was reversed by addition of excess of L-arginine but not D-arginine (1 mM). 4. In high K+ (40-60 mM)-contracted rings, ACh was a much less effective vasodilator and its relaxant response was completely abolished by L-NOARG (100 microM). 5. In NA (10 microM)-contracted rings, ACh induced sustained and concentration-dependent increases in cyclic GMP, which were reduced below basal values by L-NOARG (100 microM), while potent relaxation persisted. Similar increases in cyclic GMP were evoked by ACh in high K+ (50 mM)-treated arteries and under these conditions, both cyclic GMP accumulation and relaxation were L-NOARG-sensitive. 6. S-nitroso-L-cysteine (NC), a proposed endogenous precursor of endothelial NO, also induced cyclic GMP accumulation in NA-contracted oviductal arteries. 7. Methylene blue (MB, 10 microM), a proposed inhibitor of soluble guanylate cyclase, inhibited both endothelium-dependent relaxation to ACh and endothelium-independent response to exogenous NO, whereas relaxation to NC remained unaffected. 8. The L-NOARG-resistant response to ACh was not affected by either ouabain (0.5 mM), glibenclamide (3 microM), tetraethylammonium (TEA, 1 mM) or charybdotoxin (50 nM), but was selectively blocked by apamin (0.1-1 microM). However, apamin did not inhibit either relaxation to ACh in high K(+)-contracted rings or endothelium-independent relaxation to either NO or NC. 9. Apamin and MB inhibited ACh-induced relaxation in an additive fashion, suggesting the involvement of two separate modulating mechanisms. 10. These results suggest that ACh relaxes bovine oviductal arteries by the release of two distinct endothelial factors: a NO-like substance derived from L-arginine, which induces cyclic GMP accumulation in smooth muscle, and another non-prostanoid factor acting by hyperpolarization mechanisms through alterations in apamin-sensitive K+ conductance.